Poor family communication and its impact on children – Field study on a sample of families in Ouargla – - kheira, Beghdadi (Journal of Humanities & Social Sciences, 2020)
The family is the main pillar in each human society as it is one of the social spaces in which the individual interacts and acquires in the context of preparations and considers family communication one of the pillars of the success of these preparations and socialization with all its components in any society and if family communication is not available the family loses its balance and this reflects on the future of the children. Our study came to reveal the dimensions and effects of the absence of communication within the family by following the variables and indicators that break up the relational foundations in the field and allow us to identify the phenomenon and follow it up by linking its variables. To achieve this in practice, the researcher used the descriptive approach, and the questionnaire was the tool of the study. The study reached many results, the most important of which were: that communication in the family does not exist between couples and in its absence, the educational level of the child will be weak as a result of the absence of supervision from the father's side.
Keywords: family; family communication; socialization; academic achievement; social domain